Research on the Deformation Law and Stress Distribution Characteristics of Overburden under the Influence of Multiple Faults - Yaobin Qi; Weijian Yu; Desun Yu; Hanxiao Guo; Bao Pan (Advances in Civil Engineering)
Taking the geological conditions of a coal mine in Liupanshui City, Guizhou Province, as the background. The fracture law of the roof in the coal face and the height of the “Two zones” were obtained through theoretical analysis and empirical formula calculation, and the results were verified using similar simulation experiments. Through numerical simulation were researched the stress distribution characteristics of the overlying strata on the working face under the influence of multiple faults. The results showed that in the early stage of mining, F1 undergoes activation under the influence of the main roof weighting, leading to an increase in the degree of plastic damage to the coal seam and strata behind the working face, causing a redistribution of the behind abutment pressure. Finally, under the influence of the F1 barrier effect, the vast majority of the behind abutment pressure is transferred to the lower strata of F1, leading to a continuous increase in stress concentration there. But as the working face continues to advance, the blocking effect of the roof plastic zone above the goaf on the transmission of the behind abutment pressure of the working face begins to appear and continues to increase, leading to a decrease in the peak stress at the lower strata of F1. The stress change process on the F2 side is similar to that on the F1 side, the front abutment pressure is initially distributed in the strata in front of the working face, but as the activation degree of F2 continues to intensify, it gradually shifts to the lower strata of F2, and ultimately the majority of the front abutment pressure is borne by the lower strata of F2.